Does Intellectual Capital and Board Characteristics Affect Financial Performance? - Galuh Tresna Murti; RR. Sri Saraswati; Yuki Mayumi Yorianti (Fakultas Ekonomi Universitas Negeri Manado, 2023)
The purpose of this study was to analyze the influence of intellectual capital factors and characteristic boards on the financial performance of insurance subsector companies from 2017 to 2022. A quantitative research approach was used, and 12 insurance subsector companies were selected, so that the number of samples selected was 72 research observation data points. This study uses panel data regression analysis techniques. The findings of this study state that the intellectual capital component has a positive influence on financial performance. On the other hand, board characteristics (board size, board diversity, and board compensation) are not factors that can improve financial performance. The implication is that the insurance sub-sector companies will uphold added value through the contribution of physical capital, human capital, and structural capital to gain a competitive advantage that differentiates them from other sectors.